A Study of Unpublished Anthropomorphic Terracotta Figurines from Ancient Yemen - Al-Shargabi, Dhekra AbdulJabbar (2005)
Yemen was called the Arabic Felix as it had a long history, which started in the third millennium BC and flourished throughout the kingdom of Saba, Ma'een, Qataban, and Hadhramout, Ousan and Hemyar. The Yemeni people were proficient in many aspects of life and had the capability to build a great civilization as they had many experiences, with different types of inventions, innovative arts and religious ideas at that time. This study concentrates on one of the interesting aspects of the Yemen Civilization, i.e. an art that they were skilled in. The terracotta figurines were collected from three museums: The National Museum of Sana'a, The Military Museum in Sana'a, and the National Museum of Aden. These figurines were obtained either by donation or by purchase. There are one hundred eight including female and male terracotta figurines This study involved fieldwork that was done as follows: description of the overall shape, the position of the body, the method of manufacture, the decoration and the colour. The Fabric colour was measured using Munsell Soil Colour Charts and the hardness was measured using Moh's scale. The aim was to create a database of the terracotta figurines for future references. At present, Yemen is still lacking in ancient archaeological information concerning the art and religion. The terracotta figurines from museums showed some similarity with that from other sites in Yemen and Gulf countries that came from controlling excavations and have already been dated. As a conclusion, a date was suggested in the first millennium BC-100AD period for the terracotta figurines in the Yemeni museums in Sana'a while the terracotta figurines from Aden museum were dated to the fourth millennium BC to the second millennium BC. After extensive research and reading, we suggest that the significance of these terracotta figurines were clearly used for religious function i.e., it might have served either for worship of the mother Goddess or maybe an offering as a gift to the temples and their existence in ancient houses were to bring good luck and prevent bad luck.The male terracotta figurines were very rare but they might used as God or King or horseman or temple priest .The heads figurines might used as votive objects